English Conversational Formulas - Ivanov, A. O. (1989)
This book is intended primarily for students specializing in English at pedagogical institutes, but can also be used with any students who have a good basic knowledge of English, and on refresher courses. Its aim is to present systematically the most important expressions used nowadays in everyday life and to drill them in a wide variety of situations.
Keywords: English Practice